2002
DOI: 10.1046/j.1442-9071.2002.00507.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the sub‐basal nerve plexus of the living healthy human cornea by in vivo confocal microscopy

Abstract: The purpose of the study was to perform quantitative analysis of the sub-basal epithelial nerve plexus of healthy, living human cornea,using real time in vivo confocal microscopy and the analySIS software system. The study was based on in vivo confocalmicrostructural analysis of 50 eyes of 50 subjects, divided into two age groups: group 1 (n = 25)25 +/- 5 years of age, and group 2 (n = 25) 70 +/- 5 years of age. All subjects exhibited clinically healthy corneas. The overall nerve density was 632.35 +/- 287.57 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
4
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 17 publications
7
91
4
1
Order By: Relevance
“…Although Grupcheva et al 24 have demonstrated a decrease in nerve fibre density with age, Erie et al 8 did not find a significant correlation between age and subbasal nerve fibre density. A second limitation of this study is that one cannot be certain that measurement of CCT by pachymetry and the area imaged by IVCM took place in the same area.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although Grupcheva et al 24 have demonstrated a decrease in nerve fibre density with age, Erie et al 8 did not find a significant correlation between age and subbasal nerve fibre density. A second limitation of this study is that one cannot be certain that measurement of CCT by pachymetry and the area imaged by IVCM took place in the same area.…”
Section: Discussionmentioning
confidence: 96%
“…22 These authors demonstrated that autocrine production of vasoactive intestinal peptide (VIP) by the corneal endothelium has a protective effect, having an active role in maintaining the differentiated state and suppressing apoptosis in corneal endothelial cells. 23,24 It is conceivable that both corneal endothelial cell loss occurring in FECD or other endothelial diseases, and corneal edema developing in FECD could lead to decreased levels of VIP or other neuropeptides, consequently affecting corneal nerve density and function. Conversely, the loss of corneal nerves could lead to decreased levels of neuropeptides, including VIP, subsequently resulting in endothelial cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Recent studies analyzed the morphology of the subbasal nerve plexus in normal corneas by confocal microscopy. [10][11][12] Moreover, the architecture of the corneal subbasal nerve plexus has been investigated, with the aid of confocal microscopy, in patients with keratoconus, Sjogren syndrome, or dry eye, as well as after penetrating keratoplasty, laser in situ keratomileusis, or photorefractive keratectomy. [13][14][15][16][17][18][19][20][21] Within this context, the purpose of this study was to investigate the corneal sensitivity in patients with PCG and correlate the clinical findings with the corneal subbasal nerve density by use of LSCM.…”
Section: Introductionmentioning
confidence: 99%
“…Normal corneal nerve morphology has been studied in healthy subjects by light and electron microscopy (Muller et al 1996(Muller et al , 1997) and more recently confocal microscopy (OliveiraSoto et al 2001; Grupcheva et al 2002). Several groups have employed corneal confocal microscopy to demonstrate that corneal small nerve fi ber damage is directly related to the severity of somatic neuropathy (Figure 10) (Rosenberg et al 2001;Malik et al 2003;.…”
Section: Corneal Nerve Morphologymentioning
confidence: 99%
“…Confocal microscopy has been used to show that increasing age results in a decrease in nerve fi ber density, but there is no effect on the nerve fi ber diameter or beading frequency (Grupcheva et al 2002). Several authors have demonstrated a signifi cant alteration in corneal nerve fi ber morphology in Bowman's layer of diabetic patients which have been related to the severity of somatic neuropathy (Rosenberg et al 2000;Malik et al 2003;Hossain et al 2005;Chang et al 2006).…”
Section: Bowman's Membrane (Anterior Limiting Lamina)mentioning
confidence: 99%